Prioritization of Deliveries in Manufacturing Companies Using Fuzzy QFD (2018)
The restrictions of installed capacity and distribution resources to which medium and large manufacturing companies are normally subject, make it necessary to establish methods that serve as a tool to make decisions regarding the prioritization of each of their warehouses at the time of supplying them. the importance that the distribution center assigns to each of these, is closely related to the conditions and particularities that characterize them, being these factors of a qualitative, quantitative or a mixture between the two. This article presents a fuzzy QFD multi-criteria method which, in addition to using quantitative variables to establish the order of dispatch of the finished product, considers qualitative variables, the result of the opinions that experts can offer about the particular situations of each winery by means of linguistic variables that are finally quantified through fuzzy triangular numbers.